DEVELOPMENT AND ANALYSIS OF A MATLAB GUI APPLICATION: AUTOMATIC COLOR DETECTION AND CONVERSION BASED ON RGB VALUES FOR EDUCATIONAL AND DIGITAL DESIGN - Anggraini, Devita; Fitriana, Nurin; Firmanto, Bayu; Aziz, As’ad Shidqy; Sesoca, Jendra; Kristianti, Tri; Budijanto, Arif (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The advancement of digital technology necessitates practical solutions for accurate color identification and conversion, particularly in the fields of design, education, and the digital industry. This study aims to develop and analyze an automatic color detection application based on a MATLAB GUI, capable of detecting colors from RGB input values and converting them to Hex, CMYK, and HSV formats. The urgency of this research lies in the need for an efficient, user-friendly application that minimizes errors in the color identification process, as manual methods are often ineffective and prone to mistakes. The methodology employed is Research and Development (R&D), which includes litera-ture review, needs analysis, system design, application implementa-tion, and thorough testing and evaluation of accuracy and usability. Testing results demonstrate that the application can accurately detect and convert colors, with performance consistent with standard applica-tions such as Microsoft Paint, and has received positive feedback from users regarding its intuitive interface. The implications of this research are the availability of a digital tool that supports more efficient design processes, interactive learning, and creative industry workflows, while also opening opportunities for the development of similar applications in the future